2006
DOI: 10.1097/01.coc.0000227544.01779.52
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Angiosarcoma

Abstract: Cutaneous angiosarcoma is a rare, aggressive malignancy that is optimally treated with resection and wide-field postoperative RT. The likelihood of local-regional failure is high, as is the risk of distant relapse. Chemotherapy may be useful for short-term palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
149
2
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 25 publications
5
149
2
9
Order By: Relevance
“…In terms of radiation dose, several authors generally recommend approximately 60 Gy in 30 fractions for treatment of a primary tumour [3,14]. In the current study, of the patients treated with radiotherapy only (macroscopic disease), in-field recurrence occurred in 4 of 11 patients (36.4%) treated with less than 70 Gy, while none of 14 patients treated with 70 Gy or more had in-field recurrence.…”
Section: Angiosarcoma Of the Scalp And Facementioning
confidence: 46%
See 3 more Smart Citations
“…In terms of radiation dose, several authors generally recommend approximately 60 Gy in 30 fractions for treatment of a primary tumour [3,14]. In the current study, of the patients treated with radiotherapy only (macroscopic disease), in-field recurrence occurred in 4 of 11 patients (36.4%) treated with less than 70 Gy, while none of 14 patients treated with 70 Gy or more had in-field recurrence.…”
Section: Angiosarcoma Of the Scalp And Facementioning
confidence: 46%
“…Cutaneous angiosarcomas can occur as lesions in any part of the body, but most frequently arise on the scalp and face of elderly people [1,2]. Several investigators have suggested that angiosarcomas of the scalp and face form a distinctive subgroup due to their extremely poor prognosis, with 5-year survival of only 10-15% [1][2][3]. This highly aggressive tumour spreads widely through the skin, recurs locally and metastasises early.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical intervention is limited to local control and is not recommended for widely disseminated disease. Current guidelines call for total surgical resection of the tumor with wide negative margins to reduce reoccurrence (Lahat et al 2009;Mendenhall et al 2006). However, the multicentric nature of cutaneous AS and its proximity to vital organs in visceral disease makes achieving complete tumor resection difficult.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%